1975
DOI: 10.1111/j.1600-0609.1975.tb01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Metabolism in Polycythaemia Vera

Abstract: Histamine metabolism was studied in 35 patients with polycythaemia Vera (PV) at different stages of their disease and compared with controls and patients with secondary polycythaemia. In addition to blood and urinary histamine the main urinary metabolites of histamine, methylhistamine (MeHi) and 1-methyl-4-imidazoleacetic acid (MeImAA) were measured. In patients with active PV the excretion of MeHi and MeImAA was significantly higher than in controls and secondary polycythaemia, indicating an increased histami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…32 This symptom can antedate diagnosis or appear during the course of the disease; it is poorly responsive to phlebotomy or myelosuppressive therapy, while interferon-α, 33.34 or selective serotonin reuptake inhibitors 35 can be successful. Pruritus has been associated with iron deficiency, 36 high leukocyte count, 36 platelet activation, 35 histamine release, 37,38 infiltration of the derma by mononuclear cells and eosinophils, 39 and degranulation of dermal mast cells, 39,40 but the underlying mechanisms remain substantially obscure. Furthermore, we, like others, found that pruritus was more common among patients harboring a greater than 50% V617F allele burden; 26,27,41 accordingly, we found that the number of circulating activated basophils, measured by their expression of CD63, was significantly increased in this category of patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 This symptom can antedate diagnosis or appear during the course of the disease; it is poorly responsive to phlebotomy or myelosuppressive therapy, while interferon-α, 33.34 or selective serotonin reuptake inhibitors 35 can be successful. Pruritus has been associated with iron deficiency, 36 high leukocyte count, 36 platelet activation, 35 histamine release, 37,38 infiltration of the derma by mononuclear cells and eosinophils, 39 and degranulation of dermal mast cells, 39,40 but the underlying mechanisms remain substantially obscure. Furthermore, we, like others, found that pruritus was more common among patients harboring a greater than 50% V617F allele burden; 26,27,41 accordingly, we found that the number of circulating activated basophils, measured by their expression of CD63, was significantly increased in this category of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pruritus (Latin prurire , to itch) has long been recognized as an important clinical feature of PV [4,5]. PV‐associated pruritus is often triggered by contact with water at any temperature, and is a subtype of a broader grouping termed as ‘aquagenic pruritus’ (AP) [6–8]. Pruritus has been noted in 5–69% of PV patients.…”
Section: Introductionmentioning
confidence: 99%
“…PV-associated pruritus is often triggered by contact with water at any temperature, and is a subtype of a broader grouping termed as 'aquagenic pruritus' (AP) [6][7][8]. Pruritus has been noted in 5-69% of PV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Increasedhistamine release has been touted as a potential risk factor for the peptic ulcer disease [24]. PV patients have been proven to have higher serum and urinary histamine level [26]. Increased histamine release has been associated with increases in gastric acid secretion, mucosal blood flow and mucosal permeability, hence predisposing to peptic ulcer disease [27].…”
Section: Primary Polycythemia Vera and Gastrointestinal Bleedingmentioning
confidence: 99%